1998
DOI: 10.1002/etc.5620170416
|View full text |Cite
|
Sign up to set email alerts
|

Removal, partitioning, and fate of silver and other metals in wastewater treatment plants and effluent‐receiving streams

Abstract: Abstract-We investigated the removal of silver in five publicly owned treatment works (POTWs) and the fate of Ag in effluent receiving streams. Comparisons were made to several other metals. Silver was removed efficiently (Ͼ94%) in all POTWs. The percentage of total Ag removed was independent of the influent Ag concentration, while the concentration of Ag in effluents was directly related to influent concentration. A good correlation (r 2 ϭ 0.77) between metal removal (%) and partition coefficient (K d ) indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(76 citation statements)
references
References 21 publications
7
64
1
4
Order By: Relevance
“…This is a wider range than that found by Li et al (2013) where 28-180 ng/L total was reported (Shafer et al, 1998;Adams and Kramer, 1999;Wen et al, 2002). With one exception (SB1) all the STPs, regardless of type, removed more than 93% of the particulate silver in the influent (table 2), confirming previous assessments made in the US in the late 1990s on the efficiency of silver removal in sewage treatment (Shafer et al, 1998).…”
Section: Particulate Silver (>450 Nm) In the Sewage Influents And Effsupporting
confidence: 82%
See 1 more Smart Citation
“…This is a wider range than that found by Li et al (2013) where 28-180 ng/L total was reported (Shafer et al, 1998;Adams and Kramer, 1999;Wen et al, 2002). With one exception (SB1) all the STPs, regardless of type, removed more than 93% of the particulate silver in the influent (table 2), confirming previous assessments made in the US in the late 1990s on the efficiency of silver removal in sewage treatment (Shafer et al, 1998).…”
Section: Particulate Silver (>450 Nm) In the Sewage Influents And Effsupporting
confidence: 82%
“…For the >450 nm particulate material collected on filters, the method used by Shafer et al (1998) was adopted. To get sufficient sample, three filters for the influent and 4-6 filters for effluent samples were used.…”
Section: Digestion Methods For Particulate and Colloidal Silvermentioning
confidence: 99%
“…4). Die Anreicherung im Schlamm be- (Shafer et al 1998), so sind im Ablauf einer realen Kläranlage mit rund 0,1 µg/L Ag zu rechnen.…”
Section: Pilotkläranlageunclassified
“…Beispielsweise resultiert auf Basis einer von Shafer et al (1998) berichteten mittleren Silberkonzentration von 4 µg/L Ag im Zulauf von Kläranlagen und einer durchschnittlichen Abwassermenge von jährlich 80 m einer mittleren Zulauffracht von 2,5 mg/Tag Ag pro Einwohner (Firk 1986). Diese Abschätzung führt, bei wiederum 10 Mio.…”
Section: Introductionunclassified
See 1 more Smart Citation